Vegetation Options for Increasing Resilience in Pastoral Hill Country - Tozer, Katherine; Douglas, Grant; Dodd, Mike; Müller, Karin (Frontiers in Sustainable Food Systems, 2021)
Steep, uncultivable hill country below 1000 m comprises about 40% of New Zealand’s land surface area. Hill country farmers require options to increase the resilience of their farms to climatic and economic extremes while addressing soil conservation and water quality issues. We profile and discuss two options that can assist in transforming hill country. The first comprises a simple approach to grazing management in hill country pastures to increase pasture resilience and the second approach focuses on including selected forage shrubs (and trees) to create grazed pasture-shrublands. Deferred grazing, the cessation of grazing from flowering until seed dispersal of the desirable species in a pasture, is an old practice which has novel applications to improve resilience of hill country farming systems. We draw on current research and practitioner experience to demonstrate the impact of deferred grazing on the resilience of the deferred pasture and the farm system. We propose that deferred grazing will: (i) increase resilience of a pasture by enabling it to better recover from biotic and abiotic stresses and (ii) reduce the risk of nutrient and sediment losses in hill country by increasing ground cover, rooting depth and soil structural stability. Introducing woody forage shrubs into hill country pastures is another option that can improve farm profitability and resilience to current and future economic and climatic variabilities. The extensive root networks of shrubs can increase soil structural stability and reduce the risk of soil erosion. In addition, shrubs can supply many other ecosystem services, such as forage and shelter for livestock. In this paper, we discuss: (i) the potential benefits of a grazed pasture-shrubland at farm, landscape and national scales; (ii) candidate woody exotic and indigenous forage species; and (iii) priorities for research.